2008
DOI: 10.1637/8296-032608-reg.1
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Characterization of Campylobacter in the Brazilian Production and Processing of Broilers

Abstract: Twenty-two commercial broiler flocks and their carcasses, totaling 546 samples (450 collected from a poultry farm and 96 from a slaughterhouse), were surveyed for the presence of Campylobacter. The positive results for Campylobacter among the analyzed samples were homogeneous, yielding 81.8% for cecal droppings, 80.9% for feces, and 80.4% for cloacal swabs. Pre-enrichment and direct plating showed that 77.85% and 81.8% of cloacal swabs, respectively, were positive for Campylobacter compared to 99.0% and 97.9% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 13 publications
2
3
0
1
Order By: Relevance
“…Because there are few reports on flock prevalence of Campylobacter in South Asia the results were compared with other tropical countries. The prevalence observed in the current study is similar to that observed in Tanzania 69.8% [ 28 ] and in Brazil 80% [ 29 ]. Reunion Island, which is situated in the Indian Ocean, reported a prevalence rate of 54% in their broiler flocks [ 30 ].…”
Section: Discussionsupporting
confidence: 89%
“…Because there are few reports on flock prevalence of Campylobacter in South Asia the results were compared with other tropical countries. The prevalence observed in the current study is similar to that observed in Tanzania 69.8% [ 28 ] and in Brazil 80% [ 29 ]. Reunion Island, which is situated in the Indian Ocean, reported a prevalence rate of 54% in their broiler flocks [ 30 ].…”
Section: Discussionsupporting
confidence: 89%
“…The isolates displayed high phenotypic resistance to tetracycline (94.17%), erythromycin (87.03%), ampicillin (97.08%), and ciprofloxacin (76.25%). In Brazil, studies have shown that there is a high prevalence of quinolones (72.2%), tetracycline (43%), erythromycin (38.9%), and ampicillin (26.9%) resistance in Campylobacter in circulation [87,88]. In Bolivia, Argentina, Chile, and Peru, many Campylobacter strains are resistant to quinolones (47-78%) as well as tetracycline (40.8-65.9% in Argentina and Bolivia), erythromycin (58.6% to 61.4% in Bolivia and Chile), and ampicillin (47.2% in Argentina) [89].…”
Section: Discussionmentioning
confidence: 99%
“…After enrichment in Bolton broth to boost low cell numbers in some samples, all pre- and post-chiller carcass samples tested positive. However, these data were higher than those reported by the Europeans, who had an average poultry carcass contamination level of 75.8%, 21 and by Kuana et al, 8 who reported that 98.3% of 60 broiler carcasses were contaminated after chiller processing. In the present work, a significant difference was found between the Campy-Cefex and mCCDA plates used for cell recovery in the analysis of pre-chiller carcass samples, where Campy-Cefex had higher Campylobacter cell numbers ( Table 2 ).…”
Section: Discussionmentioning
confidence: 53%
“…Broiler carcasses contaminated with Campylobacter have been detected in many countries. A study conducted in Brazil 8 showed that 95 of the 96 broiler carcasses examined tested positive for Campylobacter at the end of the slaughter line. According to the World Health Organization, 9 reducing the prevalence or concentration at a specified point in the production chain has the potential to reduce the risk of human incidences if intervention is taken.…”
Section: Introductionmentioning
confidence: 99%